2019
DOI: 10.2106/jbjs.18.00898
|View full text |Cite
|
Sign up to set email alerts
|

Pedaling-Based Protocol Superior to a 10-Exercise, Non-Pedaling Protocol for Postoperative Rehabilitation After Total Knee Replacement

Abstract: Background: Despite Total Knee Replacement (TKR) patients routinely receiving physical therapy in the immediate and early post-operative phase, there is a paucity of research into the optimal exercise protocols in both the acute inpatient setting and early period after discharge. The acute period after TKR has become increasingly important for post-operative rehabilitation as average length of stay (LOS) rates decline worldwide. Pedaling has often been recommended by clinicians after TKR for rehabilitation, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Stationery cycling is recommended and widely used in rehabilitation after TKA which has been the stimulus for the development of a cycle muscle power test [ 11 ]. This has been facilitated by the availability of power meter cranks and pedals which can be fitted to a road bicycle or spin bike.…”
Section: Introductionmentioning
confidence: 99%
“…Stationery cycling is recommended and widely used in rehabilitation after TKA which has been the stimulus for the development of a cycle muscle power test [ 11 ]. This has been facilitated by the availability of power meter cranks and pedals which can be fitted to a road bicycle or spin bike.…”
Section: Introductionmentioning
confidence: 99%
“…There were 64 (57%) studies that had mentioned exercise adherence within their study [ 18 , 19 , 22 – 24 , 27 , 29 , 31 , 33 , 34 , 36 – 38 , 42 – 47 , 50 , 53 , 54 , 58 , 59 , 63 , 65 – 69 , 73 , 74 , 78 , 79 , 82 – 84 , 86 , 90 – 93 , 96 – 100 , 102 – 104 , 107 – 109 , 111 , 112 , 114 , 117 , 118 , 121 , 123 , 126 , 127 , 129 , 131 ]. Of these studies only 41 (65%) reported sufficient information (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies only 41 (65%) reported sufficient information (e.g. measurement used and outcome) to assess exercise adherence [ 19 , 22 , 31 , 33 , 34 , 36 , 38 , 42 – 45 , 53 , 58 , 66 – 68 , 74 , 78 , 79 , 82 , 83 , 86 , 90 – 93 , 96 – 98 , 102 – 104 , 107 – 109 , 112 , 114 , 117 , 123 , 126 , 127 ]. There were 15 studies that had a pre-defined cut-off for exercise adherence (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most effective physiotherapy exercise protocol during the acute hospital stay is based on restoring safe functional mobility and performing exercises with a focus on increasing knee range-of-motion such as bike pedalling (Figures 1-3). 30 In 2019, a randomised controlled trial investigated early exercise therapy protocols after TKR surgery and was published in the Journal of Bone and Joint Surgery. It showed that a simple self-directed, low-cost, three-exercise bike pedalling-based protocol was superior to a therapist-led standard multi-exercise regimen, for both functional and patientreported outcomes.…”
Section: Early Mobilisation and Exercise Therapymentioning
confidence: 99%
“…It showed that a simple self-directed, low-cost, three-exercise bike pedalling-based protocol was superior to a therapist-led standard multi-exercise regimen, for both functional and patientreported outcomes. 30 Based on the results of this trial, patients who have had a TKR can complete a few simple home-based exercises -focusing on bike pedalling, knee extension and heel-toe walking practice -for the first two weeks following their knee surgery and expect optimal outcomes. Following this early recovery , patients yet to gain 90-degree knee flexion or those who are having difficulty progressing with their mobility may benefit from some supervised physiotherapy treatment, with no significant difference shown between patients supervised in the home or outpatient setting.…”
Section: Early Mobilisation and Exercise Therapymentioning
confidence: 99%